2015
DOI: 10.1038/srep11566
|View full text |Cite
|
Sign up to set email alerts
|

Network-based survival-associated module biomarker and its crosstalk with cell death genes in ovarian cancer

Abstract: Ovarian cancer remains a dismal disease with diagnosing in the late, metastatic stages, therefore, there is a growing realization of the critical need to develop effective biomarkers for understanding underlying mechanisms. Although existing evidences demonstrate the important role of the single genetic abnormality in pathogenesis, the perturbations of interactors in the complex network are often ignored. Moreover, ovarian cancer diagnosis and treatment still exist a large gap that need to be bridged. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…Indeed, we found that Mesenchymal or Immunoreactive MRs were detectable in the majority of TCGA samples (78%) at different levels of activation. Furthermore, there is an emerging consensus that network-based biomarker candidates, especially with sound biologic rationale, often exhibit high reproducibility and sensitivity in ovarian cancer 45 46 . The facts that stroma-associated MRs predicted clinical outcome and that Mesenchymal and Immunoreactive MRs differentially linked to opposite prognostic categories prompted us to deduce that the stromal composition and interplay might have a significant, if not major, contribution to the HGS-OvCa prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that Mesenchymal or Immunoreactive MRs were detectable in the majority of TCGA samples (78%) at different levels of activation. Furthermore, there is an emerging consensus that network-based biomarker candidates, especially with sound biologic rationale, often exhibit high reproducibility and sensitivity in ovarian cancer 45 46 . The facts that stroma-associated MRs predicted clinical outcome and that Mesenchymal and Immunoreactive MRs differentially linked to opposite prognostic categories prompted us to deduce that the stromal composition and interplay might have a significant, if not major, contribution to the HGS-OvCa prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the functional modules we identified, 33 module pairs of UC and CRC were observed in total that significantly shared overlapping DEGs with a P value cutoff of 0.05 computed by MCODE algorithm ( Supplementary Table 4 ). Overlapping genes have been extensively recognized as versatile factors involved in a variety of phenotypically diverse disease states [ 14 , 15 ]. We therefore explored those overlapping DEGs to produce the first dimension explanation of the connections.…”
Section: Resultsmentioning
confidence: 99%
“…They can be also used as a monitor when cells become cancerous, because cancerlectins can catch the instantaneous change of the glycosylated molecule, which distributes on the cells membrane, when the cell turns cancerous. In other words, cancerlectins can be the marker of tumor tissue-derived cells 9 10 11 12 . For example, Helix Pomatia agglutinin is an useful prognostic indicator in colorectal carcinoma 13 .…”
mentioning
confidence: 99%